2006
DOI: 10.1007/s11663-006-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of equilibrium relations in managanese ferroalloy production

Abstract: The complex heterogeneous equilibria associated with the production of manganese ferroalloys have been simulated using recently developed thermochemical databases. Over 600 measured equilibrium data have been used to verify and calibrate the model calculations. Good agreement is obtained for many important technical relations such as carbon solubility, equilibrium diagrams and phase relations, and element distribution as a function of temperature and composition. Experimental slag/metal and slag/metal/gas equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…1) Graphite is the stable phase in the lower Si range, whereas silicon carbide (SiC) becomes the stable phase at higher Si content, e.g. 22 mass% Si when [C]ϭ1.0 mass% at 1 773 K. 4) Therefore, the addition of Si decreases the solubility limit of carbon in SiMn alloy melt, resulting in a nucleation and growth of SiC particles in the melt. The carbide particles are believed to float up and partly dissolve into the slags at slag/metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…1) Graphite is the stable phase in the lower Si range, whereas silicon carbide (SiC) becomes the stable phase at higher Si content, e.g. 22 mass% Si when [C]ϭ1.0 mass% at 1 773 K. 4) Therefore, the addition of Si decreases the solubility limit of carbon in SiMn alloy melt, resulting in a nucleation and growth of SiC particles in the melt. The carbide particles are believed to float up and partly dissolve into the slags at slag/metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the carbon solubility predicted with FactSage is very similar to that predicted by Tang and Olsen (2006), if slightly lower (see Figure 2). Most importantly for this discussion, the silicon content at double saturation of the metal (saturation with both graphite and silicon carbide) is essentially the same; see Table III.…”
mentioning
confidence: 66%
“…In the cases where solid precipitation was allowed to proceed to equilibrium (Figure 5), the proportion of graphite-saturated melts was even smaller (Table VIII); this is because SiC precipitation (which would occur in SiC-saturated melts) would remove carbon from solution, moving the metal composition even further from graphite saturation. Where the calculations were based on the Tang and Olsen (2006) database, the calculated activities of SiC and C, were lower than for FSstel (Table VIII).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Batra, 2003;Slizovskiy & Tangstad, 2010;Tang & Olsen, 2004) Concerning the modelling of these processes, it is necessary -as it is in the production of ferrochrome -to know the influence of the electric current on the physical and chemical properties and phenomena within the furnace. In the thermodynamic modelling of the ferroalloys production systems, the most important phases to be modelled are the liquid slag and the metal alloy itself (Tang & Olsen, 2004). Despite the existing similarities, production of each ferroalloy has also its own characteristic features that needs to be taken into account in the modelling of these processes.…”
Section: Saf In the Production Of Other Ferroalloysmentioning
confidence: 99%